Minimal invasive surgical algorithm for revision lumbar spinal surgery - Lee, Yu Chao (J Spine Surg, 2019)
BACKGROUND: Revision spinal surgery following primary spinal fusion procedure occurs in 8–45% of cases. Reasons for revision include recurrence of stenosis, non-union, implant failure, infection, adjacent segment degeneration and flat back fusion. With the rise in elective lumbar fusion rates, it is expected that the rate for revision spinal surgery will also increase with time. The use of minimal invasive surgical techniques for revision spinal surgery is controversial. Careful patient and technique selection is important in achieving satisfactory outcome in revision spinal surgery. METHODS: This article outlines our algorithm for selecting the appropriate minimally invasive surgery (MIS) techniques for revision lumbar spinal surgery. Surgical options range from decompression employing MIS techniques to open osteotomies, but the optimal approach comes down to two deciding factors: (I) nature of previous surgery and (II) spinopelvic parameters. RESULTS: Representative revision cases managed using MIS techniques based on proposed revision algorithm are presented. CONCLUSIONS: Our proposed algorithm provides surgeons with a systematic approach in selecting the appropriate combination of MIS techniques for revision lumbar spinal surgery based on pathology and sagittal alignment.